"CLINICAL AND SURGICAL OUTCOMES OF DORSAL SPINE INTRADURAL EXTRAMEDULLARY SPACE-OCCUPYING LESIONS: A PROSPECTIVE INSTITUTIONAL EXPERIENCE" - Dr. Hazi Zawar Sadiq Abbas, Dr. Hazi Zawar Sadiq Abbas; Dr. Hazi Zawar Sadiq Abbas, Dr. Raja Raajan; Dr. J. Srisaravanan (Student’s Journal of Health Research Africa, 2024)
Background Space-occupying lesions (SOLs) within the spinal canal can cause compression and distortion of nearby neural tissue. These lesions create space by causing atrophy in the surrounding spinal tissue, leading to neurological deficits. While advancements in neuroimaging techniques have significantly transformed neurologic diagnosis in recent decades, the definitive diagnosis of any central nervous system SOL still requires histological examination of tissue obtained through surgical biopsy. Aims To assess the outcome of space-occupying lesions in the spinal region and assess the prevalence of different lesions, including their clinical characteristics based on age, gender, compartmental distribution, and the specific spinal levels affected. Materials and methods In this prospective study spanning 1 year at a well-equipped tertiary care hospital in India with a neurosurgery department, 12 specimens (biopsy and surgical) from spinal cord and adjacent structure lesions were examined. The study included indoor patients from the neurosurgery department exhibiting clinical signs, symptoms, and imaging features indicative of spinal space-occupying lesions (SOL). Exclusions comprised primary bone tumors and congenital anomalies, including vascular malformations not involving the cord. Results The prevalent age group affected was 41-60 years, with an average age of 47 years, and a higher incidence among females. Neoplastic lesions constituted the majority at 87%, primarily benign or low-grade. Meningioma emerged as the most frequent histologic diagnosis, followed by schwannoma. Conclusion Tissue diagnosis is crucial given the diverse range of lesions in the spinal region, each with distinct prognoses and treatment approaches. Recommendations Early diagnosis and prompt surgical intervention are essential for managing dorsal spine intradural extramedullary lesions, attention should be given to common diagnoses like meningiomas and schwannomas, to ensure timely and effective treatment.